Hydrologic data from a firn aquifer in Southeast Greenland, 2015-2016 - Miller, Olivia; Solomon, Kip (Arctic Data Center, 2019)
The Greenland ice sheet is losing mass, which can contribute to sea level rise. Firn aquifers covering between 22,000 – 90,000 km2 have recently been discovered within the ice sheet. In summer, surface snowmelt infiltrates to depth, saturating pore space within the compacting firn. Recharge ceases when the surface temperatures cool below 0ºC in the fall. Instead of refreezing, the meltwater stays in liquid phase throughout the year because of the insulation produced by high snow accumulation rates. This liquid flows through the firn, and discharges from the aquifer, likely to crevasses at the edge of the ice sheet. Flow through the firn behaves according to Darcy’s law. Instead of permanently storing meltwater, either through refreezing or simple storage in pore space, firn aquifers allow large volumes of meltwater to discharge from the ice sheet. The fate of that meltwater and its pathways to the ocean remain unknown and require further work as some scenarios (e.g., hydrofracturing crevasses leading to basal lubrication) could play important roles in accelerating ice flow and discharge to the ocean. This dataset contains field data from a series of tests to characterize the hydraulic properties of a firn aquifer in Southeast Greenland. The aquifer and slug tests are meant for estimating the hydraulic conductivity of the firn aquifer. Aquifer tests were conducted by pumping water out of a borehole and measuring the water level change within the aquifer. Slug tests were conducted by lowering the water level in a sealed piezometer installed in the aquifer by pumping air into it and measuring the water level recovery upon venting the piezometer. The borehole dilution tests, which measured the decrease in specific conductance following injection of saltwater into a borehole over time as freshwater flows through the aquifer, are meant to measure the rate of liquid flowing through the firn aquifer.